Juridical Analysis of Hotel Building Permits In The City Center: Administrative Compliance and Environmental Impact Study of Velmont Hotel Construction In Bukittinggi City - Prima Febriansyah; Afriva Khaidir (Peneliti.net, 2026)
The growth of the tourism sector has driven an increase in hotel development in downtown areas, including in the historic tourist city of Bukittinggi. The construction of Hotel P, located in the strategic Jam Gadang area, has sparked debate regarding administrative compliance, spatial planning suitability, and urban environmental impacts. This study aims to analyze the compliance of the Hotel P construction permit process with state administrative law provisions, spatial planning regulations, and environmental protection instruments. The study uses a normative juridical approach combined with empirical juridical analysis of regulations, licensing documents, and urban environmental data from 2020 to 2022. Environmental impacts are analyzed using an Environmental Pressure Index based on Principal Component Analysis (PCA), which includes indicators of waste volume, noise levels, and reduction of green open spaces. The results of the study indicate inconsistencies between licensing documents and actual conditions in the field, weak licensing transparency, and a significant increase in environmental pressure. This study emphasizes the importance of strengthening administrative law enforcement, integrating environmental evaluation into the licensing process, and applying the principles of good environmental governance in hotel development in urban core areas. Translated with DeepL.com (free version)